The Effects of Adaptive Gamification in Science Learning: A Comparison Between Traditional Inquiry-Based Learning and Gender Differences - Alkinoos-Ioannis Zourmpakis; Michail Kalogiannakis; Stamatios Papadakis (Computers)
Gamification has become a topic of interest for researchers and educators, particularly in science education, in the last few years. Students of all educational levels have consistently faced challenges when grasping scientific concepts. However, the effectiveness of gamification, especially in terms of academic performance, has shown mixed results. This has led researchers to explore a new alternative approach, adaptive gamification. Our study compared the effects of adaptive gamification with traditional inquiry-based learning. Two classes of 9-year-old students participated, with the experimental group using adaptive gamification and the control group following a more conventional teaching approach using inquiry-based lessons and experiments. Both groups were tested before and after the lessons, and their results were analyzed using SPSS. The findings revealed that while both groups showed a significant difference after the lessons, the experimental group had significantly higher scores than the control group. Particularly significant results were observed regarding learning improvements based on students’ gender, with female and male students in the experimental group demonstrating significant improvement. In contrast, in the control group, only the male students displayed significant learning improvement. This research contributes significantly to the relatively new field of adaptive gamification in science education and the improvement of students’ science learning, particularly in the context of gender differences.